The Importance of Increasing Minimum Age For Marriage In Indonesian Marriage Law - Holijah, Holijah; Abd Manaf, Jariyah Binti (Universitas Islam Negeri Raden Intan Lampung, 2019)
This article discusses the changes in the minimum age for marriage as regulated in Law Number 1 of 1974 concerning marriage, which was later amended by Law No. 16 of 2019 on the same topic. In Law no. 1/1974, the minimum age for marriage for the prospective groom and bride is differentiated in which for the prospective groom the minimum age for marriage is 19 years while for the bride is 16 years. This kind of distinction was later removed by Law No. 16 of 2019 which stipulates the minimum age for marriage for the prospective groom and bride to be the same, namely 19 years. This change in minimum limits is really important as it can have positive effects, especially for women, as they can be physically and psychologically ready to become a wife as well as a mother for their children. Indeed, physical and mental maturity for someone intending to get married is important. This is also following the principles of Islamic Law which view that marriage requires physical and spiritual readiness and that the family is the main source for producing quality human beings.